Վիկտորյա Աղանուրյանի գրական ժառանգությունը - Անահիտ Սևումյան (ՀՀ ԳԱԱ հրատ.)
События и поэтические традиции 1890-1900-х годов ярко отразились на художественной мысли и поэзии Виктории Аганурян. Поэтесса родилась в 1855 г. Она жила и творила в Италии. Несмотря на то, что ее стихотворения с большим интересом воспринимались современниками — армянскими и итальянскими критиками, тем не менее ее творчество не удостоилось достаточного внимания литературоведов. Events and poetic traditions of the 1890s-1900s reflected brilliantly on Victoria Aghanuryan's artistic idea and poetry. The poetess was born in 1855. She lived and created in Italy. Though her poems were accepted by her contemporaries - Armenian and Italian critics with great interest, no one has paid enough attention to her work.
Keywords: Biography; Literature; Auxiliary Sciences of History; Language and Literature